(untitled) (International Journal of Medical and Surgical Sciences, 2018)
Objective: To evaluate the in-vitro antimicrobial effect of Titanium alloys with Copper Nanoparticles (CuNP) against Streptococcus mutans and Phorphyromonas gingivalis . Materials and Methods: An in vitro study was carried out. The unit of analysis corresponded to 10 healing abutments. In 5 abutments Copper nanoparticles (CuNP) electrodeposition was applied. The remaining 5 abutments corresponded to control. The healing abutments were then immersed in culture medium for S. mutans and P. gingivalis for 14 days. Results: The agar plates with CuNP-coated abutments showed a lower growth, statistically significant for both bacterial strains. Conclusion: There is a statistically significant lower growth of S. mutans and P. gingivalis in healing abutments with CuNP.